An improved thermal estimation model of the inverted planetary roller screw mechanism. (December 2018) - Qiao, Guan; Liu, Geng; Ma, Shangjun; Shi, Zhenghong; Wang, Yawen; Lim, Teik C
The inverted planetary roller screw mechanism has recently become competitive in the electro-mechanical actuation system due to its high load-carrying capacity and small assembly size. However, a significant amount of heat at the frictional contact interfaces and power loss inside the electrical machine can be naturally generated in a compact and high-load inverted planetary roller screw mechanism system. The conductive heat leads to the temperature rise of inverted planetary roller screw mechanism components that subsequently results in thermal drift and error as well as the actuation accuracy degradation. An analytical approach is applied to calculate the friction torque of the contact pairs and support bearings in the inverted planetary roller screw mechanism system. As the thermal load, heat generation is derived from the friction in nut-roller-screw section and bearings. Then, the heat generation and convection boundary conditions are formulated to facilitate thermal behavior analysis. Finally, using the finite element method, steady-state and transient thermal-mechanical coupling analyses are performed to estimate the temperature distribution and thermal expansion of the inverted planetary roller screw mechanism components. Computational results reveal that operating conditions of rotation speed and external load have significant influence on the thermal characteristics of the inverted planetary roller screw mechanism. This study can serve as a foundation for modeling temperature field and analyzing coupled thermal-mechanical response of inverted planetary roller screw mechanism in electro-mechanical actuation system, which can be useful in determining thermal error compensation.